Put the steps in order to simplify the expression: 17y - 10 + 3 (2y + 1).

NOTE: Start with the given expression.
(4 points)

= Original expression: 17y - 10 + 3 (2y + 1)

= Rearrange to see like terms: 17y + 6y - 10 + 3

= Combine like terms: 23y - 7

= Do the distributive property: 17y - 10 + 6y + 3

1 answer

To simplify the expression \( 17y - 10 + 3(2y + 1) \), here are the steps in the correct order:

  1. Original expression: \( 17y - 10 + 3(2y + 1) \)
  2. Do the distributive property: \( 17y - 10 + 6y + 3 \) (where \( 3 \times 2y = 6y \) and \( 3 \times 1 = 3 \))
  3. Rearrange to see like terms: \( 17y + 6y - 10 + 3 \)
  4. Combine like terms: \( 23y - 7 \)

So the correct order is:

1, 4, 2, 3